An insight into the electrocatalysis of uranyl sulphate on gold nanoparticles modified glassy carbon electrode. (1st February 2015) - Guin, Saurav K.; Parvathi, K.; Ambolikar, Arvind S.; Pillai, Jisha S.; Maity, Dilip K.; Kannan, S.; Aggarwal, Suresh K.
Graphical abstract: Abstract: Monodispersed gold nanoparticles (AuNPs) were prepared on glassy carbon electrode by multiple galvanostatic pulse strategy in the absence of any template or additional chemicals. The cyclic voltammetry, differential pulse voltammetry, electrochemical impedance spectroscopy experiments and quantum mechanical calculations were performed to unravel the mechanism of electrocatalytic reduction of uranyl (U VI O2 2+ ) by AuNPs. The higher density of states of 5d band of gold nanoparticles and its strong interaction with the LUMO(U-5f) of [U VI O2 ( η 1 -OSO3 )( η 2 -O2 SO2 ), 2H2 O] 2− was found to be the most probable reason for catalyzing the heterogeneous electron transfer reaction. This is the first report on the participation of the 5f-orbital of actinyl ion in the electrocatalysis at AuNPs.